Periodicals Ukraine as a Means to Promote the Theory and Practice of Childrenʼs Movement in the 20ʼs – Early 30-ies of XX Century - Karpych, Iryna (Pedagogical Discourse, 2013)
The article analyzes Ukrainian periodicals as a means of promoting the theory and practice of childrenʼs movement in the 20ʼs–early 30ʼs of the twentieth century. According to the direction of the Periodical Press author distributes various editions of Ukraine into the following groups: special «child Periodicals», educational journals and Comsomol periodicals. The periodical press importance for the development of childrenʼs movement in Ukraine is stressed. Periodicals programs and the main problems of childrenʼs movement in the pages of periodicals are covered.